Oliver Tambo International Airport, South Africa: Land-Use Conflicts Between Airports and Wildlife Habitats - Robinson, Lance; Mearns, Kevin; McKay, Tracey (Frontiers in Ecology and Evolution, 2021)
Airports stimulate tourism and trade and are a vital link in any country’s tourism infrastructure and economy. Large airports such South Africa’s busiest airport the OR Tambo International Airport, in Ekurhuleni, Gauteng, are located on the periphery of cities, usually on land that forms part of the peri-urban economy, often reserved for farming or left undeveloped. At the same time, such land is usually a wildlife haven compared to neighbouring more ‘urbanized’ or developed areas. This places wildlife, especially birds on a collision course with aircraft. So much so that bird and other animal strikes cost the aviation industry millions of dollars annually. Therefore, it is essential to reduce the number of wildlife strikes, not only lower the risk of damage to aircraft, increase passenger safety and reduce operational delays, but also prevent a decline in local wildlife populations. This paper argues that South Africa needs to manage land use close to airports in such a manner that it minimises the potential for bird and animal strikes. This study catalogues different habitats and land-use types surrounding OR Tambo International Airport, identifying potential bird hazard zones using kernel density analysis. The results determine which areas pose the highest potential risk in terms of bird strikes. It was found that land-use and land zoning within the International Civil Aviation Organisation (ICAO) recommends a 13 km zone around airports must take surrounding land-use into account to mitigate bird strikes. This entails airport operators working with land-use planning authorities and neighbouring stakeholders.